Formative Assessment in An Online Class of Language Learning: Literature Review - Hernik Farisia (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2021)
Abstract: Such published research provided the concept of formative assessment but the current practices of assessment for language learning digital based were weak. Therefore, this study intended to analyse and synthesize the results of relevant literature from any previous research to build a conceptual framework of using formative assessment and feedback in the digital age to promote a greater impact on reading achievement at elementary school. The literature selection was carried out using Publish or Perish (PoP) and screened by Convence.org program to records the eligible’ literature. A total of 8 articles were included in the analyses. The analyses of the text revealed that technology plays a role in enhancing communication and feedback among teachers, students, and peers, even though parents. In an online class of language learning, teachers could conduct an assessment interactively with various learning activities and such various digital-based instruments. It provided teachers current information about students’ reading development through dynamic formative feedback cycles including teaching, assessing, and adjusting diverse instruction to meet students’ need in learning.Abstrak: Penelitian yang dipublikasikan tersebut memberikan konsep penilaian formatif tetapi praktik penilaian saat ini untuk pembelajaran bahasa berbasis digital masih lemah. Oleh karena itu, penelitian ini dimaksudkan untuk menganalisis dan mensintesis hasil literatur yang relevan dari penelitian sebelumnya untuk membangun kerangka konseptual menggunakan penilaian formatif dan umpan balik di era digital untuk mempromosikan dampak yang lebih besar pada prestasi membaca di sekolah dasar. Seleksi literatur dilakukan dengan menggunakan Publish or Perish (PoP) dan disaring oleh program Convence.org untuk mencatat literatur yang memenuhi syarat. Sebanyak 8 artikel dimasukkan dalam analisis. Analisis teks mengungkapkan bahwa teknologi berperan dalam meningkatkan komunikasi dan umpan balik antara guru, siswa, dan teman sebaya, bahkan orang tua. Dalam pembelajaran bahasa kelas online, guru dapat melakukan penilaian secara interaktif dengan berbagai kegiatan pembelajaran dan berbagai instrumen berbasis digital tersebut. Ini memberikan informasi terkini kepada guru tentang perkembangan membaca siswa melalui siklus umpan balik formatif yang dinamis termasuk mengajar, menilai, dan menyesuaikan instruksi yang beragam untuk memenuhi kebutuhan siswa dalam belajar.